Leadership and resolution of conflict among Koronadal B'laan - Legarde, Aileen
The period before 1940 could be considered the period Koronadal B'laan maintained their absolute indigenous structure. However as time went on, Christians invaded their place, and this led to the deterioration of their cultural beliefs and practices. This particular study is an in depth exploration on the leadership and resolution of conflict and the changes it took through time among Koronadal B'laan. The traditional political structure of Koronadal B'laan was kinship-based. The settlement was led by a Bong fulong who they believed was the oldest and wisest man in the community. He maintained order and peace in the village. When conflict occurred he resolved it through their traditional method of conflict such as al maliw, saklang luas, and askalot. The influx of Christian migrants to the area led to the deterioration of their indigenous structure, due to the influence brought by Christianity and the imposition of national laws. Eventually, there was shift of governance, as well as changes in the resolution of conflict. Furthermore, the creation of Indigenous People Rights Act of 1997 brought back the Indigenous People, the B'laan, into the mainstream of society. Consequently, the B'laan had an independent political structure separate from the local government, leading to the restoration of their customary law.